EFEKTIVITAS GEMPAR TERHADAP PENINGKATAN PENGETAHUAN GIZI SEIMBANG MASYARAKAT PAGERBATU - Fadhli Aulia Rahman; Ardhi Jaya Satria; Randin Faridah; Thea Raina; Muhammad Rifqi Keiza Syam; Zakia Lailatu Rahma; Ade Khairani Putri; Resa Ana Dina (Ikatan Sarjana Gizi Indonesia, 2025)
The community service activity Gerakan Masyarakat Peduli Gizi dan Kemandirian Pangan (GEMPAR) was carried out as an effort to improve mothers’ knowledge of balanced nutrition through education on the concept of “Isi Piringku,” the limitation of sugar, salt, and fat consumption, the importance of complementary feeding, and the provision of supplementary food in Pagerbatu Village, Pandeglang Regency. This activity was attended by 22 mothers of toddlers on July 15, 2025, using interactive lectures, discussions, question-and-answer sessions, and cooking demonstrations with local food ingredients. Knowledge evaluation was conducted through pre-test before the activity and post-test after the activity. The results showed an increase in the average score from 47 percent in the pre-test to 73 percent in the post-test. The greatest improvement was observed in the understanding of “Isi Piringku,” limiting sugar, salt, and fat consumption, and complementary feeding, while the understanding of specific supplementary food for pregnant women and malnourished toddlers remained relatively low. The conclusion of this activity is that educational methods combined with practical demonstrations can enhance participants understanding of balanced nutrition, and similar programs are recommended to be implemented continuously with wider participant coverage and supported by interactive learning media to strengthen comprehension and encourage sustainable changes in household nutrition practices.